2016
DOI: 10.1136/bmjspcare-2015-001016
|View full text |Cite
|
Sign up to set email alerts
|

‘A Friend in the Corner’: supporting people at home in the last year of life via telephone and video consultation—an evaluation

Abstract: A nurse led, 24/7 telephone and video consultation service can provide valuable support for patients identified to be in the last year of life and for their carers. The line enabled them to feel supported and remain in their place of residence, hence reducing the pressure for avoidable hospital admissions and use of other services. Providing this service may encourage healthcare professionals to identify more patients approaching the last year of life, widening support offered to this group of patients beyond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(108 citation statements)
references
References 14 publications
(19 reference statements)
0
101
0
Order By: Relevance
“…ICT introduced at this earlier stage may be driven by the likelihood of less advanced disease with fewer complications. For palliative care patients that engage with technology, benefits to its use are only beginning to be understood, such as enabling patients to feel supported and remain in their place of residence (22). For those with pain, ICT systems are being developed to increase selfmanagement (through incorporating education components and information provision) (23) but their effectiveness for pain management has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…ICT introduced at this earlier stage may be driven by the likelihood of less advanced disease with fewer complications. For palliative care patients that engage with technology, benefits to its use are only beginning to be understood, such as enabling patients to feel supported and remain in their place of residence (22). For those with pain, ICT systems are being developed to increase selfmanagement (through incorporating education components and information provision) (23) but their effectiveness for pain management has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…45 The literature on telephone consultations consists largely of small and heterogeneous primary studies, most of which had practical challenges or methodological flaws. Systematic reviews have tended to conclude that, although telephone contact may allow minor problems to be dealt with without a face-to-face visit (and sometimes with apparent cost-savings), it may miss rare but serious conditions and/or lead to higher rates of face-to-face visits in the days following.…”
Section: Telephonementioning
confidence: 99%
“…34,35 One study combined telephone consulting with video consultation to support patients receiving palliative care and reported that the combination offered both practical support and reassurance. 45 …”
Section: Telephonementioning
confidence: 99%
See 2 more Smart Citations